Inequality and legitimacy in global governance: an empirical study - Jongen, Hortense; Scholte, Jan Aart (European journal of international relations, 2022)
This article undertakes an empirical investigation of the relationship between structural inequalities and legitimacy beliefs in global governance. Normative theory often emphasises inequality as a major source of injustice in global politics, but we lack empirical research that examines the implications of inequality for legitimacy in concrete situations of global governance. This paper draws on large mixed-method survey evidence regarding inequality perceptions and legitimacy beliefs at the Internet Corporation for Assigned Names and Numbers (ICANN), a key site of global Internet governance that has given particular priority to issues of diversity and inclusion. Our analysis arrives at four main findings. First, participants in ICANN do perceive substantial structural power asymmetries and often find them to be problematic. Second, persons on the perceived subordinate side of these power stratifications tend to observe larger inequalities and to find them more problematic than persons on the perceived dominant side. However, third, these perceptions and concerns about inequality almost never associate with legitimacy beliefs towards ICANN, even among people in structurally subordinated positions and among people who express the greatest worries regarding power inequalities. Fourth, in forming legitimacy perceptions, participants at ICANN generally prioritise other aspects of institutional purpose, procedure and performance, unconnected with inequality. This lack of a relationship between perceptions of inequality and legitimacy beliefs suggests that, however sympathetic policy elites at ICANN might be towards greater equality in principle, they are unlikely to give it precedence in practice.